Barriers and Facilitators of Implementation of the Non-Hospital-Based Administration of Long-Acting Cabotegravir Plus Rilpivirine in People with HIV: Qualitative Data from the HOLA Study - Diana Hernández-Sánchez; Juan M. Leyva-Moral; Julian Olalla; Eugènia Negredo; on behalf of the HOLA Study Group (Viruses)
Long-acting (LA) antiretroviral therapies for human immunodeficiency virus (HIV), such as injectable formulations of cabotegravir and rilpivirine (CAB+RPV LA), are now available. Considering the limited data on the out-of-hospital administration of this combination, evaluating the implementation strategies needed is essential to support future clinical efforts. To gather data on barriers and facilitators of implementation for CAB+RPV LA in alternative outpatient facilities, this study used qualitative interviews informed by the Consolidated Framework for Implementation Research (CFIR), with 13 staff participating in the HOLA study (NCT06185452). Data analysis followed qualitative descriptive methods, assisted by Atlas.ti software version 22. The study adhered to the COREQ guidelines. Findings reveal five main factors to consider for implementation: operational and infrastructure adaptations, integrated management of human and organizational resources, need for coordination and follow-up, professional attitudes and work environment, and patient experience and patients’ needs perceived by professionals. This study emphasizes the comprehensive operational and infrastructure adaptations, adequate staff training, and supportive professional environment required for the successful implementation of CAB+RPV LA, while considering patients’ needs throughout the externalization process (trial registration number: NCT06643897).